HUBUNGAN KOMUNIKASI ORANG TUA DAN KESEPIAN DENGAN ADIKSI INTERNET DI SITUASI PANDEMI COVID-19 PADA REMAJA DI SMA NEGERI 1 PAGAR ALAM SUMATERA SELATAN - Febby Fereza, (2021)
The phenomena of internet addiction is one of the health problems in Indonesia. In adolescents this is increasing with the number of adolescents with internet addiction behavior, due to internal factors (loneliness) and external factors (parental communication). This study discusses the relationship between parental communication and loneliness with internet addiction during the covid-19 pandemic of adolescents at sman 1 Pagar Alam Sumatera Selatan. Research using Chi-Square test with survey analytic with cross-sectional design. Sampling totaling 189 adolescents and sampling technique uses purposive sampling. The results of this study indicate there is a relationship between parental communication with internet addiction (p value = 0,001). There is a relationship between loneliness with internet addiction (p value = 0,034). Adolescents should reduce risk and prevention by overcoming internet addiction such as building positive and open communication with parents and participating in positive activities.